2018
DOI: 10.1371/journal.ppat.1006789
|View full text |Cite
|
Sign up to set email alerts
|

Tomato leaf curl Yunnan virus-encoded C4 induces cell division through enhancing stability of Cyclin D 1.1 via impairing NbSKη -mediated phosphorylation in Nicotiana benthamiana

Abstract: The whitefly-transmitted geminiviruses induce severe developmental abnormalities in plants. Geminivirus-encoded C4 protein functions as one of viral symptom determinants that could induce abnormal cell division. However, the molecular mechanism by which C4 contributes to cell division induction remains unclear. Here we report that tomato leaf curl Yunnan virus (TLCYnV) C4 interacts with a glycogen synthase kinase 3 (GSK3)/SHAGGY-like kinase, designed NbSKη, in Nicotiana benthamiana. Pro32, Asn34 and Thr35 of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 74 publications
4
90
0
Order By: Relevance
“…Our previous studies have demonstrated that C4 interacts with NbSKh (Mei et al, 2018). This raised a possibility that TLCYnV C4 is a substrate of this kinase.…”
Section: Phosphorylation Of Tlcynv C4 By Nbskh Is Critical For C4-indmentioning
confidence: 98%
“…Our previous studies have demonstrated that C4 interacts with NbSKh (Mei et al, 2018). This raised a possibility that TLCYnV C4 is a substrate of this kinase.…”
Section: Phosphorylation Of Tlcynv C4 By Nbskh Is Critical For C4-indmentioning
confidence: 98%
“…Geminivirus C4/AC4 protein appears to exhibit similar functions to human viral ''oncogenes''. In support of this, Mei et al (2018b) showed that TLCYnV C4 induces cell cycle progression by sequestering SKh kinase, an inhibitor of cyclin CycD1;1. This action results in the accumulation of CycD1;1, which can then form a complex with CDK in the nucleus, enabling transition of the cell from G1 to S phase, and this ensures viral genome replication (Mei et al, 2018b).…”
mentioning
confidence: 87%
“…In support of this, Mei et al (2018b) showed that TLCYnV C4 induces cell cycle progression by sequestering SKh kinase, an inhibitor of cyclin CycD1;1. This action results in the accumulation of CycD1;1, which can then form a complex with CDK in the nucleus, enabling transition of the cell from G1 to S phase, and this ensures viral genome replication (Mei et al, 2018b). These findings suggest that the ability of C4/AC4 to induce hyperplasia and tumorigenic growth in infected plant tissues is at least partially due to C4-mediated sequestration of SKh from the nucleus.…”
mentioning
confidence: 87%
See 2 more Smart Citations